Changing Is Not Vanishing : a Collection of American Indian Poetry to 1930. - Parker, Robert Dale (University of Pennsylvania Press, 2011)
Changing Is Not Vanishing simultaneously reinvents the history of American Indian literature and American poetry by uncovering a vast but forgotten archive of early American Indian poems. The book includes work by 82 writers and a full bibliography of poems by more than 140 Indian writers who wrote before 1930.